2021
DOI: 10.2147/opth.s314943
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Web-Based Reading Test for Normal and Low Vision Patients

Abstract: Purpose To develop and validate a web-based reading test for normal and low vision patients. Methods This is a prospective, comparative trial. The web-based Democritus Digital Acuity Reading Test (wDDART) was developed. wDDART introduces a series of advanced characteristics (advanced text calibration, computer-vision-based estimation of patient’s distance, and automatic calculation of patient’s reading times) that facilitate the overall examination procedure. wDDART’s r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Preoperative clinical examination included assessment of the corrected distance visual acuity (CDVA) and the corrected near visual acuity (CNVA) with the Greek version of the democritus digital acuity & reading test (Democritus University, Alexandroupolis, Greece), corneal topography, mesopic pupil, chord-mu and coma evaluation with the Topolyzer Vario (Alcon Laboratories, Inc.), and contrast sensitivity with the Pelli-Robson test at 85 cd/m 2 at background light. 21,22 Postoperative examination included distant and near uncorrected visual acuity (UDVA and UNVA, respectively) with the democritus digital acuity & reading test, dysphotopsia by 2 direct 4-scale, Likert-type questions (1: always; 2: most of the times; 3: sometimes; 4: never) pertaining on the subjective perception of glare and unwanted shadows, as described before, and satisfaction rates with the Greek version NEI-VFQ 25, 6 months after the operation of the second eye. 23…”
Section: Data Collectionmentioning
confidence: 99%
“…Preoperative clinical examination included assessment of the corrected distance visual acuity (CDVA) and the corrected near visual acuity (CNVA) with the Greek version of the democritus digital acuity & reading test (Democritus University, Alexandroupolis, Greece), corneal topography, mesopic pupil, chord-mu and coma evaluation with the Topolyzer Vario (Alcon Laboratories, Inc.), and contrast sensitivity with the Pelli-Robson test at 85 cd/m 2 at background light. 21,22 Postoperative examination included distant and near uncorrected visual acuity (UDVA and UNVA, respectively) with the democritus digital acuity & reading test, dysphotopsia by 2 direct 4-scale, Likert-type questions (1: always; 2: most of the times; 3: sometimes; 4: never) pertaining on the subjective perception of glare and unwanted shadows, as described before, and satisfaction rates with the Greek version NEI-VFQ 25, 6 months after the operation of the second eye. 23…”
Section: Data Collectionmentioning
confidence: 99%
“…Recently, our group developed the Democritus Digital Acuity and Reading Test (DDART) and published its validation outcomes for near and intermediate vision assessment. 10,11 Our results suggested that the DDART is a reliable web-based test for near and intermediate vision evaluation that can be used in telemedical settings.…”
mentioning
confidence: 82%
“…As previously reported, DDART was developed in collaboration with the Department of Computer Science and Biomedical Informatics of the University of Thessaly. 10,11 Brief Presentation of DDART DDART is a web-based application that has been validated as a reading acuity test. 10,11 In this work, DDART's functionality has been extended to simulate a series of prevalent distance vision tests as well; among them are the ETDRS, the Snellen, the Landolt C, and the Tumbling E. Therefore, DDART can be used to evaluate dVA in telemedical settings, provided that a highresolution screen with internet access is present.…”
Section: Settingmentioning
confidence: 99%
“…The following clinical indices were evaluated: a) binocular uncorrected near visual acuity (UNVA), b) binocular uncorrected intermediate visual acuity (UIVA), both using the web-based Democritus Digital Acuity Reading Test (wDDART) [ 17 , 18 ], and c) spherical equivalent.…”
Section: Methodsmentioning
confidence: 99%